Xylanases of Bacillus spp. isolated from ruminant dung as potential accessory enzymes for agro‐waste saccharification. (12th February 2015) - Thite, V.S.; Nerurkar, A.S.
Abstract Polysaccharide hydrolase producing bacteria were isolated for biomass saccharification step in two‐step bioethanol production. Xylanolytic bacteria were found to be common in ruminant dung. Seven Bacillus dung isolates exhibited high xylanolytic activity; three of which were identified as Bacillus safensis and four as Bacillus altitudinis, based on 16S rDNA and gyrB gene sequencing. Interestingly, comparison of activity profiles for B. safensis M35 and B. altitudinis R31 and J208 crude xylanases showed activity in similar temperature and pH ranges of 40–60 °C and 6·0–9·0, respectively, even though they were isolated from three different dung sources. Furthermore, 22–28% viscosity reduction of beechwood xylan substrate by all the three xylanases points towards their endo‐acting nature. Endo‐acting xylanases are envisaged as accessory enzymes which help expose the cellulose fibres for the subsequent action of the core enzyme cellulases. In this study, when supplemented to the commercial cellulase as a cocktail, the accessory role of the crude xylanases from the selected Bacillus strains was established as 1·3, 2·33 and 1·9 fold increase in saccharification of barley husk, sugarcane bagasse and wheat husk was achieved, respectively. Significance and Impact of the Study The uncontrolled use of fossil fuels and concerns about its future availability, have invoked interest over unconventional alternative energy sources like solar, hydropower, geothermal, nuclear and biomass. Plants, being largest renewable biomass on earth, have received consideration as a source of biofuels. Ruminant dung isolates M35, R31 and J208 belonging to Bacillus sp. produces majorly endo‐xylanase when induced with wheat bran. Such plant cell wall degrading endo‐xylanases with broad pH optima and mesophilic nature can act as accessory enzymes with cellulases to enhance the saccharification of plant biomass in biofuel industries.